The impact of science and technology towards rural community in understanding Islam /Abdul Hapes Mohammed and Nurul Diana Mohamed Iqbal - Mohammed, Abdul Hapes; Mohamed Iqbal, Nurul Diana (2015)
Islam has derived into this world to bring civilization to mankind. It is a gift from Allah to all human beings on this earth. After an extensive period of Islam based in Malaysia since the time of the Malacca Sultanate, it has grown swiftly and become the official religion of Malaysia. As we know, this country is now moving towards the developed countries. Innumerable efforts and initiatives engaged by the government to safeguard that Malaysia continues to advance in all aspects and one of it is science and technology. This is aligned with our country’s Vision 2020, “The sixth is the challenge of establishing a scientific and progressive society, a society that is innovative and forward-looking, and one that is not only a consumer of technology but also a contributor to the scientific and technological civilization of the future”. That’s why it’s a requirement for us to understand and mastering the skills in the arena of anything you want endeavour. Things would be much easier with the support of science and technology. This paper will show how science and technology can contribute a positive influence to the community, especially for those living in rural areas regarding the understanding the matters of Islam which related in their lives.